Investigating the Effectiveness of Schema Therapy on Negative Perfectionism and Obsessive Thoughts in a Group of Patients with Obsessive-Compulsive Disorder - Mokhber, Mahnoosh; Tahaei, Seyedeh Marzieh; Kavousi Sarjoo, Marziyeh; Yarhosseini, Mahdeseh; Moghadasan Neyshabouri, Nasrin (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to examine how schema therapy can help reduce negative perfectionism and obsessive thoughts in a group of individuals diagnosed with OCD. Methods and Materials: The current study was a quasi-experimental research project that involved a pre-test, post-test, and a follow-up phase lasting three months, with both control and experimental groups. The study focused on clients with a history of obsessive-compulsive disorder who sought treatment at psychology clinics in Tehran during the summer and fall of 2023. The sample size consisted of 32 individuals selected through purposive sampling methods. The educational program consisted of seven sessions lasting 90 minutes each, held twice a week at the research location. The research utilized the Positive and Negative Perfectionism Scale (PANPS) and the Maudsley Obsessive-Compulsive Inventory (MOCI) to measure outcomes. Data analysis was performed using SPSS version 27 software, employing descriptive statistics (mean and standard deviation), repeated measures ANCOVA, and Bonferroni and Kruskal-Wallis H post hoc tests at a P-value of 0.05.Findings: Based on the research results, the P-value for Between-Subjects Effects showed significance between the experimental and control groups when analyzing negative perfectionism and checking variables (p